2005
DOI: 10.1007/s11661-005-0290-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitrogen in the cyclic deformation behavior of duplex stainless steels

Abstract: The role of nitrogen in the cyclic deformation behavior of duplex stainless steels (DSS) has been studied under fully reversed total-strain amplitude. The cyclic hardening-softening curves show that cyclic stress levels become lower with increasing nitrogen content. The cyclic softening becomes more evident with increasing nitrogen content. It can be attributed to the greater strength of austenite than that of ferrite as plastic strain is accumulated beyond the critical strain. This is achieved by a higher str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Nitrogen in solid solution also modifies the behaviour of dislocations by changing the slip mode from wavy to planar slip. Previous investigations have attributed to DSS a typical behaviour of softening or hardening/softening especially when alloyed with nitrogen [6,15]. By another way, it has been shown that development of planar arrangements of dislocations is most of the time associated with a softening of the material.…”
Section: Effect On Stress Responsementioning
confidence: 99%
“…Nitrogen in solid solution also modifies the behaviour of dislocations by changing the slip mode from wavy to planar slip. Previous investigations have attributed to DSS a typical behaviour of softening or hardening/softening especially when alloyed with nitrogen [6,15]. By another way, it has been shown that development of planar arrangements of dislocations is most of the time associated with a softening of the material.…”
Section: Effect On Stress Responsementioning
confidence: 99%
“…[27][28][29][30][31][32] To summarize their conclusions, it may be said that plastic deformation occurs initially in austenite, but the rapid strain hardening of this phase leads to an early plastic transfer to ferrite. Afterward, cyclic softening results mainly as a consequence of strain localization in ferrite.…”
Section: A Hardening-softening Responsementioning
confidence: 99%
“…This fact is in agreement with the high nitrogen content of the studied duplex steel (0.24 pct) and also the strong partitioning of this element to austenite that elevates this value to around 0.60 pct. [32] It is well known that nitrogen reduces the stacking-fault energy and therefore enhances planar slip character. [37,38] On the other hand, a trend toward wavier features was observed at intermediate temperatures, as explained in Section III-B.…”
Section: Substructural Features Associated With Cyclic Deformationmentioning
confidence: 99%
“…In general, the excellent properties of nitrogen-alloyed steels are attributed to the ability of nitrogen to stabilize austenite and refine the second phase. 1,2 For nitrogenalloyed Fe-Cr-N series steels, recent investigations mainly focus on the following aspects. Hertzman et al 3 carried out thermodynamic analysis on Fe-Cr-C-N and Fe-Cr-Ni-N systems in the temperature range of 1273-1473 K. Uebing et al 4 studied the surface segregation of Cr and N in Fe-15%Cr-N single crystal at 490-750 °C.…”
Section: Introductionmentioning
confidence: 99%